(untitled) (Tribhuvan University Law Journal, 2025)
Product liability serves as a fundamental pillar of consumer protection within the broader framework of commercial law. It ensures that manufacturers, distributors, and sellers are held legally responsible for releasing defective products into the market that pose risks to consumer safety. This accountability helps maintain trust in the marketplace by providing consumers with legal recourse in cases of harm or injury caused by faulty goods. In essence, product liability laws are designed to protect consumers from unsafe products, encouraging businesses to adhere to quality and safety standards to avoid potential lawsuits. The article delves into the legal landscape governing product liability in Nepal, offering a detailed examination of the relevant statutes, particularly the Consumer Protection Act, 2075 (2018). It addresses the rights of consumers to seek redress when harmed by defective products and the corresponding obligations imposed on businesses to ensure the safety and reliability of their goods. The article scrutinizes the practical aspects of how product liability claims are processed within the Nepali legal system, highlighting existing gaps and challenges that hinder consumers from successfully pursuing compensation. For example, judicial delays, lack of consumer awareness, and weak regulatory oversight often obstruct the timely and fair resolution of such claims. In addition to exploring the domestic legal framework, the article offers a comparative analysis of international standards in product liability, drawing from jurisdictions such as the United States and the European Union. These regions have more established consumer protection mechanisms, where strict liability is imposed on manufacturers, meaning they can be held liable even if they exercised due care. Comparing these legal models, the article suggests that Nepal could benefit from adopting similar provisions, which would strengthen the protection of consumer rights and enhance product safety. This comparative perspective provides valuable insights into how Nepal might reform its legal structures to foster a more consumer-friendly environment, aligning with global best practices.